FIRE FIGHTING AND RESCUE STRATEGY IN FIRE DISASTER HANDLING IN BANTUL REGENCY - Khairunnisa, Ratih; Putri, Nadya Anggara (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2024)
Fire is one of the most frequent disasters in Bantul Regency. The increase and decrease in the number of fire disasters require fast and precise handling by the Fire and Rescue Department. This study analyzes various strategies and efforts that have been made by the Fire and Rescue Department of Bantul Regency in dealing with fire disasters in Bantul Regency. In this research, a qualitative approach was used. The data collection techniques were interviews, observations, and documentation. The results showed the Fire and Rescue Department have integrated three main aspects in their strategies, namely objectives, policies, and programs. The formulated objectives formulated have met the criteria that are clear, measurable, have a time limit, and are relevant to the formulation of the strategy. In addition, existing policies have supported the strategies while providing limitations on operational actions. The designed programs have also been aligned with the established strategies. However, several policies and programs have not been able to be implemented optimally due to budget constraints and lack of personnel. Keywords: Strategy, Disaster Management, Fire, Fire And Rescue, Bantul Regency.